MITIGASI BYCATCH DAN OPTIMALISASI TANGKAPAN MELALUI BUBU RAMAH LINGKUNGAN - Ilham Fajri; Inda Mardhatillah; Tarmizi Tarmizi (Jurnal Abdi Insani, 2026)
Fishermen in Lhok Keluang, Jaya District, Aceh Jaya Regency, still predominantly use bottom gillnets, which are non-selective fishing gears that often capture non-target species such as hammerhead sharks (Sphyrna lewini) and bottlenose wedgefish (Rhynchobatus australiae), both categorized as Critically Endangered by the IUCN. This condition creates ecological and economic problems since bycatch species have low market value and threaten the sustainability of marine ecosystems. To address these issues, a community service program was conducted in the form of training and assistance on the use of environmentally friendly fish traps (bubu) as a more selective and sustainable fishing alternative. The activity aimed to enhance fishermen’s skills in constructing and operating fish traps, reduce shark and ray bycatch, and increase catches of economically valuable target species. The program was implemented in August 2025 under the coordination of Panglima Laot Lhok Keluang, involving ten fishermen, three lecturers, and two students from Universitas Syiah Kuala. The methods included focus group discussions (FGDs), socialization, training on trap construction, field implementation, and monitoring and evaluation of catches. The results showed improved fishermen’s understanding and skills in using fish traps, a decrease in bycatch, and an increase in the productivity of reef and demersal fish. Fishermen expressed their willingness to adopt this fishing method sustainably, as it is more environmentally friendly and economically beneficial. Therefore, this program successfully supported the conservation of endangered marine species, improved fishermen’s welfare, and promoted sustainable fisheries practices in the coastal area of Aceh Jaya.